Study protocol for measuring energy needs and nutritional status of adolescent girls in Abia state, Nigeria: The nutrition and adolescence in rural Nigeria (NARN’ia) Study - Mayowa T. Adegboyega; Chigozirim A. Amaeze; Chinaza P. Uche; Patricia O. Ukegbu; Herman Pontzer (PLoS ONE, 2025)
Background Adolescents in low- and middle-income countries face significant nutritional challenges, including undernutrition, micronutrient deficiencies, poor dietary habits, and food insecurity. These issues adversely affect their growth, development, and long-term health. Despite their vulnerability, adolescents are frequently excluded from nutritional program planning due to limited data, weak intervention delivery platforms, and underdeveloped policies. Methods/design The Nutrition and Adolescence in Rural Nigeria (NARN’ia) study aims to address this gap through a comprehensive assessment of energy requirements in adolescent girls (N = 70; ages 10–19 years) in Nigeria. NARN’ia will combine multiple methods: 24-hour dietary recall using the (INDDEX24 app); physical activity monitoring via accelerometry; anthropometric assessments of body composition, and the doubly labeled water method to measure total daily energy expenditure and body composition. Discussion Findings from this study will inform evidence-based nutritional guidelines tailored to adolescent girls in Nigeria. By integrating robust methodologies, NARN’ia will contribute foundational data on adolescent energy needs, supporting future research and policy development in Nigeria and other low- and middle-income countries. Trial registration ClinicalTrials.gov NCT06601959